Deep Proton Insertion Assisted by Oxygen Vacancies for Long‐Term Memory in VO2 Synaptic Transistor. (28th December 2020) - Oh, Chadol; Kim, Inseo; Park, Jaeseoung; Park, Yunkyu; Choi, Minseok; Son, Junwoo
Abstract: Reversible phase transformation of correlated oxides by field‐driven ionic process present opportunity to efficiently transduce between ionic transfer and electrical currents in insertion‐based reconfigurable transistors. However, the switching rate of insertion transistors is fundamentally limited by the slow rate of ionic insertion into the lattices of correlated oxides. Here, it is demonstrated that preformed oxygen vacancies in VO2− δ lattices strongly accelerate proton insertion by low gate voltage in synaptic transistors. As the degree of oxygen deficiency δ increases in VO2− δ transistors, the steepness of phase transformation and transconductance increase during the voltage sweep at the expense of the channel current modulation. Theoretical and experimental analyses reveal that the accelerated of H + kinetics in the VO2− δ lattice occurs because immobile oxygen vacancies reduce the energy barrier to H + migration. In an electronic synapse, this facile H + migration in VO2− δ lattices renders "inscribed" memory by positioning the H + neurotransmitter far from the electrolyte/VO2− δ interface. This discovery suggests a strategy to improve the learning and memory processes of artificial synaptic devices by controlling the density of intrinsic defects in the lattice framework to achieve efficient ion exchange. Abstract : The switching rate of insertion transistors is limited by the slow rate of ionic insertion into a channel layer. Here, it is demonstrated that preformed oxygen vacancies in VO2− δ lattices accelerate proton insertion by gate voltage in synaptic transistors. It suggests a strategy to improve the memory processes of artificial synapses by controlling the density of defects in the lattice framework.